Cement–ash concrete with the addition of lime kiln dust - Dvorkin, Leonid; Zhitkovsky, Vadim (Frontiers in Materials, 2023)
The article is devoted to the study of the effect of the lime kiln dust (LKD) on the properties of concrete mixtures and concrete using Portland cement and fly ash. A possible mechanism for the formation of the structure of cement-ash paste with the addition of the LKD is analyzed in detail. The positive effect of the LKD on hydration and structure formation due to an increase in the alkalinity of the cement-ash paste is shown. Using the method of the experiment mathematical planning, experimental-statistical polynomial models of the concrete components (Portland cement, fly ash, dust, superplasticizer, aggregates) content influence on the workability of the concrete mixture and the strength of concrete at different ages were obtained. The analysis of the obtained models was carried out, which made it possible to establish the positive effect of the LKD additive on the compressive strength of concrete at the age of 7 to 180 days.